Kebijakan Hukum Pidana Terhadap Penjualan Obat Aborsi Secara Ilegal - Antonio, Rizal Nando; Supusepa, Reimon; Fadillah, Astuti Nur (Faculty of Law Universitas Pattimura, 2025)
Indonesia, as a constitutional state, guarantees every citizen the right to health based on the principles of non‑discrimination, sustainability, and established service standards. However, the practice of illegal abortion conducted by unauthorized parties, facilitated by the distribution of restricted medications, remains a serious issue that violates legal provisions and threatens patient safety. A concrete example occurred in the city of Ternate on February 23, 2023, when Indah and Mayang performed an abortion using the drug Gastrul without medical expertise, resulting in a miscarriage. Both were charged and faced a potential prison sentence of up to ten years and a maximum fine of one billion Rupiah. This case highlights the urgent need for strict monitoring of medication distribution and consistent enforcement of the law. This research aims to review and analyze the legal policies related to the illegal sale of abortion medications, including the formulation of future criminal policies to address this practice. The method employed is normative legal research utilizing statutory, conceptual, case‑based, analytical, and historical approaches. The results of this study demonstrate that a firm criminal policy on the sale of illegal abortion medications is a vital measure by the state to prevent offenses that endanger life and violate fundamental human rights. Strict enforcement of the law, enhanced penalties, more comprehensive monitoring of drug distribution, and tighter controls over digital advertising are required. Moreover, strong support from society is essential to foster legal awareness and create an environment that safeguards future generations from the serious risks and dangers posed by illegal abortion practices. In this way, the state can effectively fulfill its constitutional obligation to protect the rights, health, and dignity of every citizen.